Effect of the application of sulphur for the control of oidiosis “leveillula taurica” in the culture of artichoke (Cynara scolymus L.) var. imperial star - Mauricio, L. (2011)
One of the important reasons for the decay of the production of artichoke is for the disease known with the name of oidium or oidiosis or ash, " Leveillula taurica ", which provokes powdery formations in the back of the leaves, and then they invade the bundle.; inducing to a loss of mass to foliate, death of the plant and reduction in performance. With the purpose of being able to offset the effect of infection and advance of the mushroom it raise the work of investigation which was to determine the suitable dose of the sulphur for the control of oidiosis (Leveillula taurica) in the culture of artichoke Cynara scolymus L var. imperial. The experiment was carried out in Victor Larco District, Trujillo, La Libertad; soil of texture clayey, a system of irrigation being used by gravity which frequency of irrigation is fortnightly for the conduction of the culture. There was used a Design of Complete Blocks at random, with four treatments and a witness, and with four repetitions. There was realized an analysis of variance and Duncan's test by a level of significant of 5 %. The results showed that the applied treatments of sulphur reduce and control the advance of the mushroom, being the best the T2, with dose 1 kg/cil. It concludes that these treatments are adapted to there be applied in the culture of artichoke for the control of oidium (Leveillula taurica).